2019
DOI: 10.1177/1933719119828042
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Immune-Related Profile Rescues Abortion-Prone Fetuses: A Novel Insight Into the CBA/J × DBA/2J Mouse Model

Abstract: The adverse clinical result and poor treatment outcome in recurrent spontaneous abortion (RSA) make it necessary to understand the pathogenic mechanism. The mating combination CBA/J × DBA/2 has been widely used as an abortion-prone model compared to DBA/2-mated CBA/J mice. Here, we used RNA-seq to get a comprehensive catalogue of genes differentially expressed between survival placenta in abortion-prone model and control. Five hundred twenty-four differentially expressed genes were obtained followed by cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The mating combination CBA/J×DBA/2 has been widely used to mimic RSA due to the characteristic high fetal resorption rate and normal karyotype [61], providing a useful system to investigate immune system-related mechanisms that lead to the rejection of the semiallogeneic embryo and to explore methods that prevent pregnancy failure [62]. Many studies have suggested that fetal absorption in this model is due to an imbalance in Th1/Th2 cells, which can amplify inflammation and result in fetal rejection [63,64], while adoptive transfer of regulatory T cells (Tregs) can reestablish maternal immune tolerance and significantly reduce fetal resorption rates [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…The mating combination CBA/J×DBA/2 has been widely used to mimic RSA due to the characteristic high fetal resorption rate and normal karyotype [61], providing a useful system to investigate immune system-related mechanisms that lead to the rejection of the semiallogeneic embryo and to explore methods that prevent pregnancy failure [62]. Many studies have suggested that fetal absorption in this model is due to an imbalance in Th1/Th2 cells, which can amplify inflammation and result in fetal rejection [63,64], while adoptive transfer of regulatory T cells (Tregs) can reestablish maternal immune tolerance and significantly reduce fetal resorption rates [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…After intraperitoneal exposure to PS-MPs, Hu et al observed a reduction in uterine blood supply and the proportion of decidual natural killer (dNK) cells while an increase of placental T helper cells, a polarization of M2 macrophage, and an immune suppressive state of cytokines ( Hu et al, 2021 ). Due to the intricacy of gestation, this result may not entirely align with our general conception ( Yi et al, 2019 ). Therefore, further research is necessary to uncover the mechanism underlying the MPs/NPs induced embryonic loss.…”
Section: Cross-generational Toxicity Of Mps/npsmentioning
confidence: 70%
“…The fetuses were small and dark, accompanied by necrosis and hemorrhage as absorbed fetuses. The absorption rate of fetuses was calculated as the number of absorbed fetuses/number of total fetuses × 100% ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%